Phytochemical Study of Eight Medicinal Plants of the Lamiaceae Family Traditionally Used as Tea in the Sharri Mountains Region of the Balkans. (19th February 2020) - Hajdari, Avni; Mustafa, Behxhet; Hyseni, Lirie; Bajrami, Ani; Mustafa, Genista; Quave, Cassandra L.; Nebija, Dashnor
Abstract : In the present study, eight plant species belonging to Lamiaceae family were identified as ingredients for herbal teas in the region of Sharri Mountains: Thymus serpyllum, Rosmarinus officinalis, Melissa officinalis, Origanum vulgare, Mentha longifolia, Ocimum basilicum, Teucrium chamaedrys, and Sideritis scardica, respectively. Chemical composition of essential oils obtained from these species was analyzed using GC-MS and GC-FID with the aim of examining their volatile compound profiles, responsible for their respective flavors and fragrance. Principal Component Analysis (PCA) was performed with the aim of grouping plant species under study on the basis of their chemical composition. Experimental data revealed the typical volatile constituent pattern for the Lamiaceae family. Monoterpenes and sesquiterpenes, responsible for flavor and medicinal use of these plants, were the most abundant groups of the volatile constituents. PCA data analysis resulted in the grouping of these analyzed species in four principal clusters.